2023
DOI: 10.1101/2023.02.01.526392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic profiling ofPlasmodium ovale wallikerirelapses with microsatellite markers and whole-genome sequencing

Abstract: Plasmodium ovale wallikeri and P. ovale curtisi were recently classified as two distinct species. Like P. vivax, both P. ovale curtisi and P. ovale wallikeri have the ability to cause relapse in humans. P. ovale spp. are still understudied and the development of genomic tools to study parasite genetic diversity parameters or medically-important traits such as relapses are needed. Here, we describe a protocol to type a set of eight putatively neutral P. ovale wallikeri microsatellite markers. Expected heterozyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Using such assays to better evaluate P. ovale parasite relatedness, transmission, and relapse patterns is critical for improving current malaria control strategies targeting P. falciparum that do not consider non-falciparum malaria species. 26,56,57…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using such assays to better evaluate P. ovale parasite relatedness, transmission, and relapse patterns is critical for improving current malaria control strategies targeting P. falciparum that do not consider non-falciparum malaria species. 26,56,57…”
Section: Discussionmentioning
confidence: 99%
“…29,34 Ultimately, samples from 25 individuals were selected for whole-genome sequencing based on higher-density P. ovale infection, lack of or lower-density P. falciparum coinfection, and balance of ovale species and geographic diversity across the sample set. Characteristics of these 25 samples, and an additional four samples from a study of P. ovale wallikeri in French travelers that were whole genome sequenced by Joste et al, 26 are shown in Supplemental Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation